THE FEASIBILITY OF UV IRRADIATION DURING PLANTS GROWTH IN THE CLOSED GROUND CONSTRUCTION - Chervinski, L.; Storozhuk, L.; Lutsak, Y. (Energy and Automation, 2016)
This article established the influence of artificial UV radiation on the process of growing plants in a greenhouses.